Enhancement of prodigiosin production by Serratia marcescens S23 via introducing microbial elicitor cells into culture medium - Thamir Mahmoud, Samer; Kadhum Luti, Khalid Jaber; Waleed Yonis, Reem (Iraqi Journal of Science, 2023)
The present study was designed to investigate the possibility of exploiting the interspecies interaction of microbial cells in order to enhance the production of prodigiosin by local isolate S. marcescens S23. Prodigiosin is a promising drug owing to its characteristics of antibacterial, antifungal, immunosuppressive and anticancer activities. S. marcescens S23 was isolated from soil sample and already recognized via morphological, biochemical and molecular identification process. The first step was to detect the optimal conditions for maximum prodigiosin production using chemically defined liquid medium. The results revealed that the optimal conditions for prodigiosin production were sucrose as carbon source; peptone as nitrogen source; 60/40% optimum C/N ratio, 2% inoculum size containing 2×109 cells/ml, which increased the production of prodigiosin from 1.72 to 416 mg/L. Elicitation experiments were carried out by introducing live and dead cells of E. coli, Bacillus subtilis and Saccharomyces cerevisiae, separately, to the S. marcescens culture at zero time. Based on the results obtained in this study, S. marcescens increased its production of prodigiosin as a result of interaction with microbial elicitor cells. The maximum enhancement was achieved in the culture elicited with the heat killed cells of E. coli at an inoculation level of 3% with an increase of approximately 9-fold, whereas the minimum enhancement was upon elicitation with live cells of E. coli and S. cerevisiae. Based on the results obtained in this study, elicitation strategy of exploiting interspecies interactions with microbial cells is successful and useful for enhancing the production of antibiotics.